Recent updates on Sintilimab in solid tumor immunotherapy - Xuhong Liu; Yong Yi (BMC, 2020)
Abstract In recent years, there have been advancements in traditional patterns of tumor therapy with the adoption of immunotherapy. Its application with or without other combined regimens has attracted attention from clinicians. Sintilimab (Tyvyt®), a highly selective fully human IgG4 monoclonal antibody, blocks the binding site of programmed cell death protein 1 (PD-1), thereby, inhibiting the interaction between PD-1 and its ligands (PD-L1/2) to restore the endogenous anti-tumor T cell responses. Sintilimab has been proven to be clinically beneficial in multiple solid tumor therapies. Combination therapy and monotherapy have shown potential and encouraging anti-tumor efficacy with controllable and acceptable toxicities. The combination therapy is more likely to be a novel and promising therapeutic option. This study provides an overview of the status of sintilimab-based clinical trials in various solid tumors.